The World Wide Web for Scientists & Engineers: A Complete Reference for Navigating, Researching & Publishing Online - Margaret Henderson (Issues in Science and Technology Librarianship)
This article reviews the book The World Wide Web for Scientists & Engineers: A Complete Reference for Navigating, Researching & Publishing Online. Bellingham, WA: SPIE-The International Society for Optical Engineering, 1998, by Brian J. Thomas.